Evaluasi Dampak Kebijakan Transportasi Suroboyo Bus dalam Menanggulangi Kemacetan di Surabaya - Richad Rendra Mulya Maulana Pratama; Endang Indartuti; Dida Rahmadanik (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
The growth in population and private vehicles in Surabaya has caused a significant increase in traffic congestion. To overcome this problem, the Surabaya City government implemented the Suroboyo Bus public transportation policy as an alternative solution. This research aims to evaluate the impact of this policy in reducing traffic jams in the city of Surabaya. The research methods used include secondary data analysis from related agencies, Suroboyo Bus user satisfaction surveys, as well as field observations at several main congestion points. The research results show that the implementation of Suroboyo Bus contributed to reducing the volume of private vehicles by 12% on main routes and increasing public interest in public transportation. However, the effectiveness of this policy still faces challenges, especially in terms of integration of transportation modes and service area coverage. In conclusion, the Suroboyo Bus policy has great potential to reduce congestion if supported by infrastructure development and increasing public awareness of the use of public transportation.